LINGUISTIC NEOCOLONIALISM IN THE CREATIVE INDUSTRY: CASE STUDY OF THE FILM OOTD: OUTFIT OF THE DESIGNER - Apriliyani, Ayu; Manshur, Ali (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2024)
This research analyzes the phenomenon of linguistic neocolonialism in the Indonesian creative industry with a case study of the film OOTD: Outfit of The Designer and its implications for English language learning. The study illuminates how the employment of English in film functions not solely as a medium of communication but also as a symbol of modernity, social status, and access to the global market. This study identifies that phenomena such as code-switching, code-mixing, and the predominance of English technical terms are indicative of power dynamics within the creative industry, thereby influencing individuals' language attitudes. Within the domain of English language acquisition, the study suggests that instrumental motivation plays a pivotal role in enhancing Willingness to Communicate (WTC) among learners. However, the study also notes that the preeminence of English can, in fact, give rise to language anxiety, particularly among students who feel less adept in their English usage. With these concerns, this study proposes the integration of translanguaging strategies and multilingual approaches within English language instruction. These methodologies are designed to foster a more inclusive and contextualized learning environment, thereby addressing the challenges posed by the dominance of English and promoting a more equitable and inclusive educational environment. By elucidating the nexus between globalization, language identity, and learning, this research offers insights into the optimal teaching of English in a balanced manner that does not disregard local language diversity.